2015
DOI: 10.1039/c4mb00591k
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth view of human serum albumin corona on gold nanoparticles

Abstract: Upon entering biological systems, such as the blood stream, nanoparticles form molecular complexes with the proteins encountered called protein coronas, which shield the surface of the exogenous nanoparticle. The most abundant blood proteins, such as albumin, initially occupy the surface of the nanoparticle. Owing to the widespread applications of gold nanoparticles in medicine, in this study, the docking of human serum albumin to gold nanoparticles was examined and the changes in protein structure were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…For AuNP-S-Tn (which possess a desorption enthapy corresponding to alkanethiols of about 167 kJ mol -1 ), 37 ssDNA strands can "tie" tightly to the surface of AuNPs with a high density, which markedly enhances the affinity and coverage, and thereby inhibits ligand exchange ( Figure 4d); 3) For BSA-stabilized AuNPs, it had previously been found that BSA can be adsorbed onto the surface of AuNPs and form a rigid corona. Although the desorption energy of BSA from AuNPs was estimated to be only in the range of several tens of kJ/mol, 38,39 the large volume of BSA significantly improved the thickness of the ligand layer, preventing ligand exchange ( Figure S5g). Thus, a simplified two- (Figure 5b, c).…”
Section: Roles Of Physisorbed Ligands In Nano-membrane Interactionsmentioning
confidence: 99%
“…For AuNP-S-Tn (which possess a desorption enthapy corresponding to alkanethiols of about 167 kJ mol -1 ), 37 ssDNA strands can "tie" tightly to the surface of AuNPs with a high density, which markedly enhances the affinity and coverage, and thereby inhibits ligand exchange ( Figure 4d); 3) For BSA-stabilized AuNPs, it had previously been found that BSA can be adsorbed onto the surface of AuNPs and form a rigid corona. Although the desorption energy of BSA from AuNPs was estimated to be only in the range of several tens of kJ/mol, 38,39 the large volume of BSA significantly improved the thickness of the ligand layer, preventing ligand exchange ( Figure S5g). Thus, a simplified two- (Figure 5b, c).…”
Section: Roles Of Physisorbed Ligands In Nano-membrane Interactionsmentioning
confidence: 99%
“…Understanding protein adsorption behavior on silica and titania surfaces is important considering their prevalence in biomedical applications [ 44 , 45 ]. HSA was selected as the model protein because it is widely studied and known to denature (via conformational changes) in the adsorbed state [ 46 , 47 , 48 , 49 , 50 ]. HSA is also a structural cognate of BSA [ 51 , 52 ], and this similarity provided the basis for comparing LSPR measurement data with past findings as further verification.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In particular, HSA has been used in fundamental studies of protein coronas formed on surfaces of nano-particles, because it is present in the corona of virtually all nanoparticles studied. [14][15][16] Although these studies provide important insights into how HSA interacts with nanoparticles, how well they reflect what occurs in more complex biological environments (e.g., in serum, or in blood plasma) has not been extensively explored. The aim of this study was to systematically compare the influence of protein coronas on the properties of functionalized polymer particles, especially their targeting abilities, by using the single model protein, HSA, and the more biologically relevant HS, a widely used in vitro model.…”
mentioning
confidence: 99%